Semiotics and Symbols in Literature (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
This article provides information about semiotics, the nature of semiotics, and symbols in literature. Semiotics and types of signs, their importance in different fields, and also in the field of literature we can see the relationship between semiotics and symbols